2022
DOI: 10.2196/36135
|View full text |Cite
|
Sign up to set email alerts
|

Dosage Frequency Effects on Treatment Outcomes Following Self-managed Digital Therapy: Retrospective Cohort Study

Abstract: Background Although the efficacy of high-dose speech-language therapy (SLT) for individuals with poststroke aphasia has been established in the literature, there is a gap in translating these research findings to clinical practice. Therefore, patients continue to receive suboptimal amounts of SLT, with negative consequences for their functional communication recovery. Recent research has identified self-managed digital health technology as one way to close the dosage gap by enabling high-intensity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Normalization is required because the numbers of progression orders vary from domain to domain, and the original number alone cannot be used to compare directly across different domains. More details of domain score and its calculation have been previously described ( 23 ). By averaging the domain score across sessions in a week (only if there are multiple sessions in a single week), it is possible to evaluate the improvement or deterioration of patients' performance over time in a single domain.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Normalization is required because the numbers of progression orders vary from domain to domain, and the original number alone cannot be used to compare directly across different domains. More details of domain score and its calculation have been previously described ( 23 ). By averaging the domain score across sessions in a week (only if there are multiple sessions in a single week), it is possible to evaluate the improvement or deterioration of patients' performance over time in a single domain.…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that in both analyses, greater practice amount would lead to better performance outcomes. Prior work has shown that during the first 10-week period of therapy, higher dosage frequency groups improved more compared to lower ones across all domains ( 23 ). Therefore, we hypothesized that such trend would persist in longer-term therapy that was practiced beyond 10 weeks.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations